2006
DOI: 10.1182/blood-2006-06-029298
|View full text |Cite
|
Sign up to set email alerts
|

Receptor activator of nuclear factor (NF)–κB ligand (RANKL) increases vascular permeability: impaired permeability and angiogenesis in eNOS-deficient mice

Abstract: IntroductionAngiogenesis, the formation of new blood vessels from a preexisting vascular bed, is a pivotal process not only in embryonic development but also in the progression of a variety of pathologic conditions. 1 A large number of molecules, which are composed of growth factors, cytokines, and lipid metabolites, are shown to be involved in pathophysiologic neovascularization by stimulating endothelial cells (ECs) directly or indirectly. 2 Some of these factors, including VEGF, often possess their abilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
67
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 38 publications
3
67
0
1
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26][27][28] Accumulating evidence also suggests that chronic subclinical inflammation has an important role in the pathogenesis of DR. An early event in the pathogenesis of diabetic vasculopathy is leukocyte adherence to retinal vascular endothelium, resulting in EC death, vascular leakage, and capillary closure. 18 Clinical evidence indicates that DMO results from breakdown of the inner blood-retinal barrier, 96 which is maintained by EC TJ complexes.…”
Section: Scientific Basismentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20][21][22][23][24][25][26][27][28] Accumulating evidence also suggests that chronic subclinical inflammation has an important role in the pathogenesis of DR. An early event in the pathogenesis of diabetic vasculopathy is leukocyte adherence to retinal vascular endothelium, resulting in EC death, vascular leakage, and capillary closure. 18 Clinical evidence indicates that DMO results from breakdown of the inner blood-retinal barrier, 96 which is maintained by EC TJ complexes.…”
Section: Scientific Basismentioning
confidence: 99%
“…104 Mukarami et al 105 and Felinski et al 101 have attempted to elucidate the mechanisms of VEGF enhancement of vascular permeability. Other factors including TNFα and interleukin (IL)-1B, 106 nuclear factor-κB (NF-κB) receptor activator, 21,22 hepatocyte growth factor (HGF), 23 and the accumulation of advanced glycation end products 20 are known to induce vascular leakage independent of VEGF-A. Adhesion molecules such as CD44 24,25 may also contribute significantly to microvascular occlusions and angiogenesis.…”
Section: Scientific Basismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the known role of RANKL in the skeletal and immune systems (13), recent studies also reported a role of RANKL in angiogenesis. Certain authors support an inhibitory role of RANKL (14,15), whereas others showed a stimulating action on angiogenesis (16). Contrary to RANKL, VEGF is known as a potent mitogen angiogenic factor and is one of the most important molecules involved in the vascularization of bone tissue (17), thus its serum levels are considered an index of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 We have also previously demonstrated additional vascular roles of RANKL in stimulating angiogenesis, expression of inflammatory adhesion molecules, and endothelial permeability. 9,10 Although RANKL has been emerging as a risk marker for cardiovascular disease, 11 the epidemiological data are still limited to ascertain clear association between RANKL level and cardiovascular disease. 6 Nevertheless, RANKL appears to be correlated with plaque destabilization and thrombosis based on its role in vascular calcium deposition and its prominent expression in advanced lesions.…”
mentioning
confidence: 99%